Pengendalian Diri dan Gaya Hidup Hedonis dalam Perilaku Konsumtif Mahasiswa: Self Control and Hedonistic Lifestyle in Student Consumptive Behavior - Muhamad Gustaf adijaya Atmaja; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Consumptive behavior among university students has become a significant issue in contemporary socio-economic and psychological discourse, particularly in relation to self-regulation and lifestyle orientation. Specific Background: Students are frequently exposed to hedonistic lifestyle patterns and digital consumption trends that shape spending behavior beyond primary needs. Knowledge Gap: Although previous studies have examined self control or hedonistic lifestyle separately, limited empirical research integrates both variables simultaneously in explaining student consumptive behavior within the same analytical model. Aims: This study aims to analyze the relationship between self control and hedonistic lifestyle with consumptive behavior among university students. Results: The findings indicate that self control is negatively associated with consumptive behavior, while hedonistic lifestyle shows a positive association. Simultaneously, both variables contribute significantly to explaining variations in student spending patterns. Novelty: This research offers an integrated empirical examination of self control and hedonistic lifestyle as concurrent predictors within a single quantitative framework. Implications: The results provide a conceptual basis for developing educational interventions and financial awareness programs targeting students to foster responsible consumption patterns. Keywords: Self Control, Hedonistic Lifestyle, Consumptive Behavior, University Students, Quantitative Analysis Key Findings Highlights: Self regulation capacity is inversely related to excessive spending tendencies among respondents. Pleasure oriented life patterns are positively linked to non-essential purchasing decisions. Combined predictors statistically explain variation in student expenditure patterns.